RETRACTED: Optimization of maintenance work by implementing an automated information system at a repair facility - Kukartsev Vladislav; Degtyareva Ksenia; Dalisova Natalia; Mazurov Alexandr; Bezvorotnykh Anastasia (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 549, 00001 (2024), https://doi.org/10.1051/e3sconf/202454900001